ASSESSMENT OF TRAINING NEEDS AND COMPETENCE LEVEL OF EXTENSION WORKERS IN KANO STATE, NIGERIA - Tafida, I.; Yusuf, A. K; Kabir, A. M.; Abdullahi, A. (FUDMA JOURNAL OF SCIENCES, 2021)
The study assessed the competence level and skills gap of extension agents in Kano State, Nigeria. Three (3) Local Government Areas were purposively selected from each of the three administrative zones making a total of nine Local Government Areas. A total of 117 extension agents were randomly selected and data were collected using structured questionnaires. Descriptive statistics, Training Needs Analysis and SWOT Analysis were used to analyse the data. The study revealed that extension services in the study area were male dominated (88.9%) and more than two third obtained Ordinary and Higher National Diplomas. Extension workers were found to understand the organizations’ needs and had the impressions that issues of the organizations can be solved through training. The study further revealed that extension workers were competent in learning initiative and enterprises (3.41), team work (3.24), communication and problem solving (3.15) while they were found to be least competent in planning and organization (2.91) and leadership (2.96). The SWOT analysis found the strength and weakness of the extension workers as transferring of information through regular interactions with farmers (3.4) and having too many jobs with different specializations (3.12) while highest ranked opportunities and threats were good communication skills with farmers (3.44) and interference of politicians into technical aspects (3.41), respectively. Therefore, frequent professional and technical trainings, employment of more extension workers especially women, disengagement of politicians from technical aspects and collaboration with research institutes and universities would improve capacity and efficiency of extension service delivery in the study area.